ANALISIS POTENSI BAHAYA PADA STASIUN GILINGAN MENGGUNAKAN JOB SAFETY ANALYSIS (JSA) DENGAN PENDEKATAN HIRARC DI PT MADUBARU - Royhan Bisma; Suseno Suseno (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The growth of industrial production activities contributes to a higher likelihood of workplace accidents, especially in work environments that involve the operation of rotating equipment. PT Madubaru (PG Madukismo) is a sugar manufacturing company located in Bantul, Yogyakarta, which recorded 11 cases of medical treatment injury at the milling station during the 2024–2025 period. This research was conducted to recognize workplace hazards, evaluate occupational risk levels, and develop appropriate control strategies by applying Job Safety Analysis (JSA) combined with the HIRARC framework. Information was obtained through field observations, interviews with supervisors and operators, as well as a review of relevant literature. The results indicate that milling activities I–V have a moderate risk level due to roll entrapment hazards and slippery floor conditions caused by bagasse and juice spillage, while the initial feeding and bagasse discharge activities are classified as low risk. Risk reduction actions were determined according to the control hierarchy, encompassing technical modifications, administrative procedures, material substitution, and the utilization of personal protective equipment.